Design and analysis of a hybrid composite drive shaft for automotive applications - Badie, Mohamed Abdel; Ebrahimi, Mahdi; Abu Talib, Abd Rahim; Abdullah, Ermira Junita; Yunus, Robiah (Federation of Engineering Institutions of Islamic Countries, 2006)
The nature of composite materials, with the advantages of higher stiffness to weight and strength to weight, facilitate a considerable reduction in the weight of torque transmission systems. The tailorability of mechanical properties of composite structure allows the optimization of the stiffness and strength throughout the drive shaft geometry to meet the requirement of traversing critical operational limitations. The main characteristic to be met in designing drive shafts is to increase the bending stiffness, which can realize a fundamental bending natural frequency that higher enough not to coincide with the rotational frequency. The shear strength, which affect the load carrying capacity and the torsional buckling strength are considered in any torque tube design. However, the torsional rigidity is linked to specific requirement; the objective of this study is to present a closeform solution procedure and utilize the results obtained from Finite Element Analysis in searching for optimum design of drive shafts.